Design and analysis of a class-aware recursive loop scheduler for class-based scheduling - ROM, Raphael (Institutional Knowledge at Singapore Management University, 2006)
In this paper, we consider the problem of devising a loop scheduler that allocates slots to users according to their relative weights as smoothly as possible. Instead of the existing notion of smoothness based on balancedness, we propose a variance-based metric which is more intuitive and easier to compute. We propose a recursive loop scheduler for a class-based scheduling scenario based on an optimal weighted round-robin scheduler. We show that it achieves very good allocation smoothness with almost no degradation in intra-class fairness. In addition, we also demonstrate the equivalence between our proposed metric and the balancedness-based metric.